2006
DOI: 10.4103/0250-474x.27818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of olibanum resin as microencapsulating agent for controlled drug delivery

Abstract: Olibanum resin was evaluated as microencapsulating agent and to prepare resin coated microcapsules. Olibanum resin coated microcapsules of indomethacin were prepared by an industrially feasible emulsification-solvent evaporation method and the microcapsules were investigated. The resin-coated microcapsules are spherical, discrete, free-flowing and multinucleate monolithic type. Microencapsulation efficiency was in the range 99-112 %. Indomethacin release from the resin-coated microcapsules was slow over 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The values of Higuchi rate constant (K H ) were found to range between 16.1 to 23.3 %h -1/2 with a distinct increasing trend as the cellulose acetate levels in the cores decreased. The effect of varying cellulose acetate levels in matrix diffusional systems on drug release has been documented 9 .…”
Section: Resultsmentioning
confidence: 99%
“…The values of Higuchi rate constant (K H ) were found to range between 16.1 to 23.3 %h -1/2 with a distinct increasing trend as the cellulose acetate levels in the cores decreased. The effect of varying cellulose acetate levels in matrix diffusional systems on drug release has been documented 9 .…”
Section: Resultsmentioning
confidence: 99%
“…8,9 However, encapsulation devices introduce a transport barrier between the host and graft tissues and inherently limit oxygen supply, compromising graft function and cell viability, 10 problems that scale with device wall thickness. 11,12 Typically grafts are implanted in subcutaneous 13 or intraperitoneal 14 sites where partial pressures of oxygen (pO 2 ) are approximately 60 and 40 mm Hg, respectively, which is lower than that of arterial blood (>80 mm Hg). It is commonly asserted that low cell viability within devices 15,16 results from low tissue oxygen taken together with device diffusional barriers to create hypoxic and anoxic conditions, where these conditions are known to promote cell death through necrosis and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Olibanum resin coated microcapsules were formulated by emulsification solvent evaporation method. It was observed that drug release from the resin-coated microcapsules was slow over 24 hours and depended on core : coat ratio, wall thickness, and size of the microcapsules [76]. …”
Section: Some Recently Investigated Natural Gums and Mucilagesmentioning
confidence: 99%